Dissolved Iron Patterns Impacted by Shallow Hydrothermal Sources Along a Transect Through the Tonga‐Kermadec Arc. Issue 7 (9th July 2022) - Tilliette, C.; Taillandier, V.; Bouruet‐Aubertot, P.; Grima, N.; Maes, C.; Montanes, M.; Sarthou, G.; Vorrath, M.‐E.; Arnone, V.; Bressac, M.; González‐Santana, D.; Gazeau, F.; et al.
Abstract: In the Western Tropical South Pacific, a hotspot of dinitrogen‐fixing organisms has been identified. The survival of these species depends on the availability of dissolved iron (DFe); however, the source of this DFe is still unclear. DFe was measured along a transect from 175°E to 166°W near 19–21°S. The distribution of DFe showed high spatial variability: low concentrations (∼0.2 nmol kg −1 ) in the South Pacific gyre and high concentrations (up to 50 nmol kg −1 ) in the west of the Tonga arc, indicating that this arc is a clear boundary between iron‐poor and iron‐rich waters. An optimal multiparameter analysis was used to distinguish the relative importance of physical transport relative to non‐conservative processes on the observed distribution. This analysis demonstrated that the shallow hydrothermal sources present along the Tonga‐Kermadec arc are responsible for the high concentrations observed in the photic layer. Nevertheless, in contrast to what has been observed for deep hydrothermal plumes, our results highlighted the rapid decrease in DFe concentrations near shallow hydrothermal sources. This is likely due to a shorter residence time of surface water masses combined with several biogeochemical processes at play (precipitation, scavenging, biological uptake, and photoreduction). This study clearly highlights the role of shallow hydrothermal sources on the DFe cycle within the Tonga‐Kermadec arc where a strong link to biological activity in surface waters can be assessed, despite the small but significant fraction of DFe ultimately stabilized. It also emphasizes the need to consider the impact of these sources for a better understanding of the global iron cycle. Key Points: Shallow hydrothermal plumes are not transported over long distances, in contrast to what has been previously reported for deep plumes Specific surface ocean conditions and chemical processes are primarily responsible for the low dispersion of shallow hydrothermal iron Nevertheless, the cumulative impact of multiple sources along the Tonga arc could fertilize the entire Lau Basin with dissolved iron